Diseño de sistema de supresión de incendios de agua nebulizada en un edificio de varios niveles en un ingenio azucarero y comparación con sistema prediseñado de gabinetes - Morales-Araya, Fabián Eliécer (Instituto Tecnológico de Costa Rica, 2017)
Water mist fire suppression systems have been under constant investigation for the last decades; however, there is still no definitive standard that provides all the parameters for its design, installation and maintenance. As a result, conventional sprinkler and cabinet systems continue to have priority in designs for all types of buildings. With the completion of this graduation project it is intended to design a water mist fire suppression system for a multi-level building in a sugar mill and compare it with a cabinet system for the same building. Once the design is done, a comparison of both systems will be made to define the advantages and disadvantages of each one, resulting in valuable information that will help clarify the doubts about the effectiveness of water mist in fire suppression
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2017.
Keywords: Agua nebulizada; Comparación; Diseño; Mantenimiento; Ingenio azucarero